Pelestarian Naskah - Naskah Kuno Di Museum Samparaja Bima Nusa Tenggara Barat - Mawaddah, Ida; Dewi Ratna Muchlisa Mandyara; Sudarsono (Jurnal Pengabdian Ahmad Yani, 2024)
Abstract Ancient manuscripts are parts of history that are written on different kinds of paper. One of the efforts to preserve the integrity of history is the preservation of ancient manuscripts. The purpose of this community dedication is to provide understanding to the community (students) regarding the importance of preserving history and the impact of loss of history. The method of implementation of this service in the community is training. This community dedication resulted in excellent responses from students, faculty, and related agencies. The answers are seen in the spirit and the questions that arise during the discussion. The conclusion of this public devotion deserves special understanding and attention as it has a positive impact on the preservation of ancient manuscripts in the Imperial Museum. It is expected to become a custom of the Bima people to preserve the history and culture of the region.  Keywords: PkM, Preservation, Manuscripts, Ancient, Bima